Tingkat Regulasi Emosi Anak Usia 5-6 Tahun di Surakarta - Maghfirota Auriza; Muthmainah; Amir Syamsudin (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Emotional regulation is one of the essential aspects of early childhood social-emotional development that plays a significant role in preparing children to face social and academic challenges. However, understanding of children’s ability to recognize, manage, and express their emotions remains limited, thus further research is needed to provide a more in-depth picture of emotional regulation levels in early childhood. The aim of this study is to explore the emotional regulation level of children aged 5–6 years. This study employed a quantitative approach with a descriptive survey method. Data were collected using a questionnaire with a Likert scale. The questionnaire consisted of 11 items and had undergone expert testing using Lawshe’s content validity as well as empirical testing using SPSS 25 for Windows. The reliability test in this study used the Cronbach’s Alpha technique, which yielded a result of 0.947, indicating high reliability. The data were analyzed using descriptive statistical analysis techniques. The results showed that most children aged 5–6 years were in the excellent category (50.54%), although some children were in the quite capable category (1.88%) and required more attention to further develop their emotional regulation. Thus, it can be concluded that, in general, early childhood children are capable of managing their emotions well in various situations. The implication of this study is the importance of the roles of parents, teachers, and policymakers in creating environments that support the development of emotional regulation in children from an early age.